A REVIEW OF THE MONKEYPOX OUTBREAK IN INDONESIA IN 2022 - Meiriani Sari; Nany Hairunisa (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Monkeypox disease (monkey smallpox) is a disease that has never been found in Indonesia since it was first discovered in humans in the Congo in 1970. So if there is one positive confirmed event, then the disease is an Extraordinary Event (KLB). This disease has become a global concern because since May 13, 2022, WHO has received reports of Monkeypox cases from non-endemic countries. It has expanded to 4 WHO regions: Europe, America, Eastern Mediterranean, and Western Pacific. Until now, further investigations and studies are still being carried out to understand more about the epidemiology, sources of infection, and transmission patterns in non-endemic countries that have reported new cases, such as Indonesia. Until now, no specific treatment has been proven to treat Monkeypox infection. Currently, the therapy used is symptomatic support. The antiviral tecovirimat, or TPOXX, developed by the European Medicines Agency (EMA) as a Monkeypox therapy in 2022 based on research, has not been marketed freely. In addition, antivirals such as cidofovir and brincidofovir have been shown to be effective against orthopox virus in vitro and in animal studies. However, the effectiveness of this drug against monkeypox in humans is not yet known. However, this disease can be prevented by vaccination. In Indonesia, the Modified Vaccinia Ankara-Bavarian Nordic (MVA-BN) vaccine is recommended to prevent Monkeypox disease. The existence of the outbreak report is important to discuss, explore, and understand more about the disease and its management and prevention.